The Effect of Helicobacter Pylori Colonization on Enterochromaffin-Like (ECL) Cell and Gastrin (G) Positive Cells in Rat Stomach - Mohammad Ali Rezaee; Mohammad Jafar Rezaie; Mohammad Reza Rahmani (مجله دانشکده پزشکی اصفهان, 2014)
Background: Enterochromaffin-like (ECL) cells have an important role in the gastric tissues. Helicobacter pylori (H. pylori) colonization has effect on function and the number of these cells. The aim of this study was to investigate the effect of 20-weeks Helicobacter pylori colonization on ECL and gastrin (G) positive cells in rat gastric tissues.